Analysis Of Leading Economic Sectors In Sidoarjo Regency - Rezzylina Dwi Akhirulyati; Parikesit Penangsang (Sean Institute, 2024)
This study aims to determine the leading economic sectors in Sidoarjo Regency. This study uses secondary data in the form of time series data from the Gross Regional Domestic Product (GRDP) of Sidoarjo Regency and East Java Province in 2014-2023. The analytical tools used in this study are: 1). Location Quotient (LQ) analysis is used to determine the basic and non-basic sectors in the economy of Sidoarjo Regency. 2). Shift Share analysis is used to determine changes and shifts in the economic structure of Sidoarjo Regency. The results of the study show that from the calculation of the LQ analysis, the basic or leading sectors in Sidoarjo Regency are three sectors, namely Electricity and Gas Procurement, Transportation and Warehousing, and the Manufacturing Industry sector. The results of the analysis show that the economic sector that has rapid growth and has a competitive advantage with rapid growth so that it has the potential to increase competitiveness is the manufacturing industry sector. Therefore, the Manufacturing Industry sector is a top priority in supporting the economic development of Sidoarjo Regency in the future.